Konsep Pendidikan Good Netizen Melalui Kurikulum Tersembunyi - Muhammad Mustaqim (Jurnal Perspektif, 2018)
This paper examines the education of good netizens through a hidden curriculum. The tendency of internet citizens who prefer to spread insults, hatred and even slander, is a problem for the school. Through an excellent netizen-based education strategy, students can be equipped with the values and character of how to use the internet and become good internet citizens. Procedures that can be done in building good netizens through hidden curricula, namely schools are expected to have an educational ideology oriented to multiculturalism, as well as a school culture that is paradigmatic of love and affection. Besides, the teacher must be able to be a good example, through the learning process, always tucking in the value of tolerance and ethics of internet usage. Finally, schools are expected to be able to build a favorable organizational climate.